2020
DOI: 10.1186/s13058-020-01330-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune parameters associated with survival in metaplastic breast cancer

Abstract: Background: Metaplastic breast carcinoma (MBC) is a rare histological type of breast cancer, which commonly shows resistance to standard therapies and is associated with poor prognosis. The immune microenvironment in MBC and its significance has not been well established due to its low incurrence rate and complex components. We aimed to investigate the diversity of immune parameters including subsets of TILs and PDL1/PD1 expression in MBC, as well as its correlation with prognosis. Methods: A total of 60 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
(53 reference statements)
2
23
0
Order By: Relevance
“…Expression of S1PR4 is restricted to lymphoid and hematopoietic tissues, and it has been shown previously that S 1 PR4- deficient mice have reduced numbers of plasmacytoid DCs (pDCs), which has been partly attributed to defects in the differentiation of pDC progenitors into mature pDCs ( Dillmann et al, 2015 ). Infiltration of immune cells, including CD4+ and CD8+ T lymphocytes and DCs into tumors, is associated with better survival of patients with TNBC ( Chao et al, 2020 ). We demonstrated herein that the expression of SGPP1 , PLPP3, and S1P receptors, particularly S1PR4, positively correlates with tumor-infiltrating DCs in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of S1PR4 is restricted to lymphoid and hematopoietic tissues, and it has been shown previously that S 1 PR4- deficient mice have reduced numbers of plasmacytoid DCs (pDCs), which has been partly attributed to defects in the differentiation of pDC progenitors into mature pDCs ( Dillmann et al, 2015 ). Infiltration of immune cells, including CD4+ and CD8+ T lymphocytes and DCs into tumors, is associated with better survival of patients with TNBC ( Chao et al, 2020 ). We demonstrated herein that the expression of SGPP1 , PLPP3, and S1P receptors, particularly S1PR4, positively correlates with tumor-infiltrating DCs in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that MBC has more tumor-infiltrating lymphocytes and showed higher PD-L1 expression in both tumor cells and stromal lymphocytes. 26 Thus, whether MBC has similarity with the immunomodulatory subtype still need to be elucidated. The more sophisticated classification of TNBC would enable us to have a better understanding of its molecular mechanism and promote the development of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were methodological and result differences among the series, all of them demonstrated that a high percentage of MBC (30 to 70%) expressed PD-L1 in tumor cells. In addition, most studies also observed higher expression of PD-L1 [ 13 , 30 , 133 , 134 , 135 , 136 , 137 ] in MBC than in other types of TNBCs. [ 30 , 133 , 135 ].…”
Section: Immune Response and Immune Therapy In Mbcmentioning
confidence: 99%
“…Thus, in the study by Joneja et al [ 30 ], although total TILs were not enumerated, it was noted that TILs vary greatly within the MBC cohort by histologic examination. Chao et al [ 134 ] found sqCC MBC exhibiting most TILs of all the MBC subtypes. Similarly, Lien et al [ 138 ] reported that sqCC exhibited the highest positivity rate of TILs, while matrix-producing carcinoma had the lowest.…”
Section: Immune Response and Immune Therapy In Mbcmentioning
confidence: 99%
See 1 more Smart Citation